Effect of a Contextual Teaching and Learning Models Based on Islamic Boarding School Culture on Students' Understanding of Mathematical Concepts - Firda Novita; Poppy Rachman; Athar Zaif Zairozie (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
The purpose of this study is to analyze the impact of using a Contextual Teaching and Learning (CTL) model based on islamic boarding school culture on students’ understanding of mathematical concepts in the topic of arithmetic sequences and series. The study employed a quantitative approach using a quasi-experimental nonequivalent control group design. The research subjects consisted of 39 eleventh-grade students at MA Nurul Hasan Maron Probolinggo, selected using purposive sampling, comprising an experimental class and a control class. Data collection was conducted through pretests and posttests, then analyzed using descriptive statistics, normality tests, homogeneity tests, independent sample t-tests, N-gain, and effect size. The results showed a significant difference between the experimental and control classes, with a significance level of 0.000 < 0.05 and a t-value of -4.724. The average score of the experimental class increased from 49.75 to 80.00, while that of the control class increased from 41.05 to 64.47. The experimental class’s N-gain value of 0.60 (moderate category) was higher than the control class’s 0.40, supported by an effect size of 1.55 (large category). These findings indicate that CTL learning based on islamic boarding school culture makes a significant difference in improving students’ understanding of mathematical concepts. This study underscores the importance of integrating local cultural contexts as a meaningful and relevant source of learning that aligns with students’ experiences in mathematics education.